Online branding - Christodoulides, George (Henry Stewart Talks, 2010)
Do we need a new theory for online branding?, Differences between online and offline branding, Developing and measuring online brand equity?, The role of trust in online branding, Addressing individual and social needs through online branding, Creating and managing an online brand experience
Archived at 2022/04/12